Knowledge, attitudes, practices, fear and stress before Covid-19 in nursing students and recent graduates in Colombia - Carreño Moreno, Sonia Patricia; Chaparro Díaz, Lorena; Cifuentes Tinjaca , Cristian David; Perilla Portilla , Freddy Elías; Viancha Patiño, Erika Ximena (Revista Cuidarte, 2021)
Introduction: The Covid-19 pandemic has affected the emotional health of human resources in health care, despite having knowledge about the virus and its management, health care personnel, including nurses, have shown stress and fear of Covid-19. Objective. To describe and correlate the level of fear, stress, knowledge, attitudes and practices regarding Covid-19 in nursing students and recent graduates in Colombia. Method. A cross-sectional and analytical observational study was conducted in Colombia between October and November 2020. The instruments of fear, stress and knowledge, attitudes and practices regarding Covid-19 were answered online by 1621 nursing students and recent graduates. Results. A mean fear score of 20.69 ± 6.1 points, a mean stress score of 89.15 ± 29.5 points and relative frequencies above 80% for knowledge, attitudes and practices to Covid-19 were observed. Direct correlations were observed between knowledge and attitudes and, in turn, attitudes with the practice. Fear was inversely correlated with knowledge and directly correlated with Covid-19 stress. Conclusion. An adequate cognitive level is observed in nursing students and recent graduates, but an emotional deficiency in the Covid-19, in terms of stress and fear. It is necessary to establish mental health support strategies for this key population in the current and future control of health crisis situations. How to cite this article: Carreño Moreno Sonia Patricia, Chaparro Díaz Lorena, Viancha Patiño Erika Ximena, Cifuentes Tinjaca Cristian David, Perilla Portilla Freddy Elías. Conocimientos, actitudes, prácticas, temor y estrés ante el Covid-19 en estudiantes y recién egresados de Enfermería en Colombia. Revista Cuidarte. 2021;12(3):e2044. http://dx.doi.org/10.15649/cuidarte.2044